Report of the Senate Committee on Confederate Relations relative to Virginia State Line : February 3, 1863 (Document (Virginia. General Assembly. Senate), 1863)
February 1863 Report of the Committee on Confederate relations recommending the transfer of the troops of the Virginia State Line to the Confederate government.